Development of a Very Sensitive ELIME Assay for Detection of sIgE to G5 and D2 Aeroallergens in Serum Samples. Issue 6 (19th May 2014) - De Stefano, A.; Volpe, G.; Adornetto, G.; Bernardini, S.; Nuccetelli, M.; Gallucci, G.; Di Ruvo, L.; Moscone, D.; Merkoçi, Arben
Abstract This work describes the development of an ELIME (Enzyme‐Linked ImmunoMagnetic Electrochemical) assay for a sensitive detection of specific IgE (sIgE) towards the aeroallergens G5 and D2 in serum samples. The system, with a detection limit of 0.1 KIU/L, uses magnetic beads as support of the immunological chain and a strip of eight‐magnetized screen‐printed electrodes, connected to a portable instrument, for a multiplexed detection. The analysis of 46 serum samples performed using both the ELIME and the Immulite 2000 assays, suggests that our method is able to measure very low concentration of sIgE and to discriminate all positive samples from negative ones.